Quantitative real-time PCR detection of a harmful unarmoured dinoflagellate, Karlodinium australe (Dinophyceae) - Nyuk, Fong Kon; Lau, Winnie L.S.; Kieng, Soon Hii; Ing, Kuo Law; Sing, Tung Teng; Hong, Chang Lim; Takahashi, Kazuya; Gu, Haifeng; Po, Teen Lim; Chui, Pin Leaw (Blackwell Publishing Ltd, 2017)
We investigated a harmful algal bloom (HAB) associated with the massive fish kills in Johor Strait, Malaysia, which recurred a year after the first incident in 2014. This incident has urged for the need to have a rapid and precise method in HAB monitoring. In this study, we develop a SYBR green-based realtime PCR (qPCR) to detect the culpable dinoflagellate species, Karlodinium australe. Species-specific qPCR primers were designed in the gene region of the second internal transcribed spacer of the ribosomal RNA gene (rDNA). The species specificity of the primers designed was evaluated by screening on the non-target species (Karlodinium veneficum, Takayama spp., and Karenia spp.) and no cross-detection was observed. The extractable gene copies per cell of K. australe determined in this study were 19 998 505 (P < 0.0001). Estimation of cell densities by qPCR in the experimental spiked samples showed high correlation with data determined microscopically (R2 = 0.93). Using the qPCR assay developed in this study, we successfully detected the 2015 bloom species as K. australe. Single-cell PCR and rDNA sequencing from the field samples further confirmed the finding. With the sensitivity as low as five cells, the qPCR assay developed in this study could effectively and rapidly detect cells of K. australe in the environmental samples for monitoring purpose.